2019
DOI: 10.1109/access.2019.2925082
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Machine Learning Techniques for Predicting Air Quality in Smart Cities

Abstract: Dealing with air pollution presents a major environmental challenge in smart city environments. Real-time monitoring of pollution data enables local authorities to analyze the current traffic situation of the city and make decisions accordingly. Deployment of the Internet of Things-based sensors has considerably changed the dynamics of predicting air quality. Existing research has used different machine learning tools for pollution prediction; however, comparative analysis of these techniques is required to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(79 citation statements)
references
References 37 publications
0
78
0
1
Order By: Relevance
“…N/S [14] AQ, MET YES To obtain a sequence pattern. N/S [39] AQ, MET NO RFR reduces overfitting, detects peak values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…N/S [14] AQ, MET YES To obtain a sequence pattern. N/S [39] AQ, MET NO RFR reduces overfitting, detects peak values.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative Analysis of Machine Learning Techniques for Predicting Air Quality in Smart Cities [39]: Ameer et al used different models for predicting air quality, such as DTR, Random Forest Regression (RFR), MLP and GBR. The dataset used in this study included year, month, day, hour, season, PM 2.5 , dew point, temperature, humidity, pressure, combined wind direction, accumulated wind speed, hourly precipitation, accumulated precipitation.…”
Section: Group 2: Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, many machine learning techniques have been proposed for solving air pollution prediction problems based on simple regression models.Authors in [3] have performed to estimate PM2.5 using random forest model and two other traditional regression models, the random forest shows the high accuracy in predicting the PM2.5 concentration. In [1] authors made a comparative study of machine learning techniques to predict the quality of air using Apache spark with multiple data sets and concluded that the random forest was a best technique in prediction but it actually work well for small size dataset and performs well only on classification problems. In [6] author proposed new model based on LSTM(Long Short-Term Memory) to forecasting PM2.5 based on the historical data and in [18] author achieves in predicting PM2.5,NO2,SO2 air pollutants concentrations with ARIMA(Auto Regressive Integrated Moving Average, Simple and Exponential Weighted Moving Average , KF algorithm and obtained the optimal result but the data handling and processing time was not discussed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Internet of Things (IoT) applications are processing growing amounts of sensor information to monitor everyday environments. Typical application examples include those supporting the elderly in smart homes [1], the ones monitoring environmental parameters in smart cities [2], smart health applications on wearable devices [3] and fault detection solutions for smart manufacturing [4].…”
Section: Introductionmentioning
confidence: 99%